Various Contemporary Intraoral Anchorage Mechanics Supported with Temporary Anchorage Devices - Delal Dara Kılınç; Gülşilay Sayar (Galenos Yayinevi, 2016)
The aim of this review was to provide an overview of the various types of contemporary intaroral anchorage mechanics that are being used with temporary anchorage devices (TADs) and to briefly mention the design and clinical use of these appliances. Original articles on "mini-implants in orthodontics, temporary anchorage devices, orthodontic miniscrews, mini-implants, and skeletal anchorage" were searched for on the PubMed database. Articles published between 2004 and May 2015 were used. References of 10 articles were also searched for and used. Beneslider, Miniscrew-supported EZ slider, Implant-supported Distal Jet, Mini-implant-Borne Pendulum B Appliance, Noncompliance-supported Maxillary Molar Distalization Appliance, Temporary Skeletal Anchorage Device-Supported Rapid Maxillary Expansion Appliance (RME), Mini-Implant-Supported Maxillary Expansion, Implant-Supported RME, Hybrid Hyrax, Frog Appliance, Palatally Anchored Mesialslider, Mousetrap Appliance, Lever Arm, and Mini-implant System were evaluated. In contemporary orthodontics, TADs have an important place. They can be combined with different intraoral mechanics and be efficiently used. The future of orthodontic intraoral anchorage may be based on TADs.